Population growth and its repercussions on agricultural lands in the coastal strip of Libya Zliten municipality as an example (Journal of Libya for geographical studies, 2024)
The research dealt with the study of population growth and its repercussions on agricultural land, and the resulting pressure on available resources, changing the pattern of land uses, and obstructing efforts to achieve sustainable development. The study aimed to track the area of ​​urban expansion on arable land through satellite images for the years 1984- 2000-2010-2020, in addition to using the Markov model for future expectations of urban expansion processes in the study area for the years 2030-2040. the study relied on the descriptive and analytical approach with the aim of determining the relationship between population growth and urban expansion, and it reached a set of results, the most important of which is that the municipality of Zliten has witnessed population growth, as it developed from 58,981 people in the year 1973 to 307,734 people during the year 2020, which resulted in an urban expansion that contributed to In putting pressure on agricultural land, the area of ​​the urban cluster has developed from 6.65 km2 in the year 1984 to 235.46 km2 in the year 2020, and it is expected to reach 340.4 km2 during the year 2040. It was found that There is a positive, statistically significant relationship of 0.896 at a significance level of 0.008 between the increasing population and the expansion of urban expansion. The study recommended the necessity of moving towards vertical urban growth in order to preserve agricultural lands.
Keywords: population growth; agricultural lands; Libya; Zliten municipality